2016
DOI: 10.1016/j.jfda.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and antioxidative activity of colored rice bran

Abstract: The profiles of bioactive compounds (including phenolics and flavonoids in free and bound fractions, anthocyanins, proanthocyanidins, vitamin E, and γ-oryzanol) of outer and inner rice bran from six colored rice samples collected from local markets were investigated. Proanthocyanidins could only be detected in red rice bran but not in black rice bran. The free fraction of the extracts dominated the total phenolics (72-92%) and the total flavonoids (72-96%) of colored rice bran. Most of the phenolic acids (83-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 26 publications
4
67
1
4
Order By: Relevance
“…The last, we believe that our results still have so many unidentified signals because of limitations of references. Some previous studies reported that there are metabolite differentiations between black rice and red rice (Yawadio et al 2007;Frank et al 2012;Na Jom et al 2016;Huang and Lai 2016;Pramai et al 2017), and our data show similar results with the previous studies mentioned.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The last, we believe that our results still have so many unidentified signals because of limitations of references. Some previous studies reported that there are metabolite differentiations between black rice and red rice (Yawadio et al 2007;Frank et al 2012;Na Jom et al 2016;Huang and Lai 2016;Pramai et al 2017), and our data show similar results with the previous studies mentioned.…”
Section: Resultssupporting
confidence: 92%
“…Pramai et al (2017) reported there are profile metabolite differentiations between black rice and red rice cultivars in Thailand. The other research also showed differentiation of metabolites between black rice and red rice (Yawadio et al 2007;Frank et al 2012;Na Jom et al 2016;Huang and Lai 2016). However, there is no information about metabolite profile differentiation between black rice and red rice in Indonesia.…”
Section: Introduc Onmentioning
confidence: 96%
“…Various studies indicated that red and black rices possess better efficacy compared to the common white rice. In addition to carbohydrate, protein, vitamins, and minerals, red and black rices are also sources of anthocyanins that are beneficial to health of antioxidants (Satue-Gracia et al 1997;Nam et al 2006;Chutipaijit et al 2011;Huang and Lai 2016), anti inflammation (Tsuda et al . 2002) and anti-cancer (Shao et al 2004;Hyun et al 2004) properties.…”
Section: Introductionmentioning
confidence: 99%
“…Pigmented rice: Pigmented rice, or colored rice, is wellknown by the rice grain having a red brown or dark purple color in its covering layers. The pigments, which are located in the aleuronic layer of rice grain, have been reported to consist of a mixture of anthocyanin compounds with a number of biological activities Chen et al, 2012;Suttiarporn et al, 2015;Hayashi and Yanase, 2016;Huang and Lai, 2016). White rice: This rice is white in color owing to removal of the hull and bran during milling.…”
Section: Different Varieties Of Rice With Medicinal Propertiesmentioning
confidence: 99%
“…White rice has fewer nutrients than pigmented rice, but is a common source of starches, syrups and flour (Abbas et al, 2011). The beneficial health components of white rice, comprises phenolic compounds, sterols, γ-oryzanol, tocotrienols and tocopherols which subsists particularly in the outer layer such as pericarp and aleurone of rice grains (Huang and Lai, 2016). Jasmine rice: Jasmine rice, which is more popularly known as "Thai fragment rice", originated from Thailand.…”
Section: Different Varieties Of Rice With Medicinal Propertiesmentioning
confidence: 99%